2005
DOI: 10.1111/j.1365-2222.2005.02378.x
|View full text |Cite
|
Sign up to set email alerts
|

Decrease of selective immunoglobulin E response to amoxicillin despite repeated administration of benzylpenicillin and penicillin V

Abstract: Subjects with selective IgE responses to side-chain-specific determinants seem to become negative, with no influence from subsequent administration of a closely related penicillin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 20 publications
1
16
0
Order By: Relevance
“…The deregulation of c-Myc confers a selective advantage on cancer cells by promoting proliferation, cell survival, and genetic instability, which can contribute to metastasis [9]. By contrast, the activation of c-Myc dramatically sensitizes cells to the apoptotic action of TRAIL by up-regulating the cell surface level of DR5 and activating DISC, thereby playing an important role in determining cellular sensitivity to TRAIL [10].…”
Section: Introductionmentioning
confidence: 99%
“…The deregulation of c-Myc confers a selective advantage on cancer cells by promoting proliferation, cell survival, and genetic instability, which can contribute to metastasis [9]. By contrast, the activation of c-Myc dramatically sensitizes cells to the apoptotic action of TRAIL by up-regulating the cell surface level of DR5 and activating DISC, thereby playing an important role in determining cellular sensitivity to TRAIL [10].…”
Section: Introductionmentioning
confidence: 99%
“…Similar patterns have been detected in patients allergic to cloxacillin or penicillin V (Padial et al 2008;Blanca-Lopez et al 2009;Romano et al 1995;Terrados et al 1995). Moreover, this recognition is maintained over time independently of the BL administered (Fernandez et al 2005). This has recently been shown with clavulanic acid (Torres et al 2010a) where patients developing an IgE response to AX-clavulanic acid administration responded to BP, AX, or clavulanic acid depending on their age.…”
Section: Cross-reactivitymentioning
confidence: 51%
“…These initial studies changed the paradigm that patients with hypersensitivity reactions to any particular penicillin should avoid penicillins altogether. Moreover, it was demonstrated that this response did not change even after repeated doses of BP and penicillin V treatment [30]. This observation, performed in a limited number of patients, was later confirmed in a larger population including 290 patients with proven IgE-mediated hypersensitivity reactions to penicillins [31].…”
Section: Penicillin As An Alternative Treatmentmentioning
confidence: 57%